Characterization of Electromagnetic Wave Propagation in Transformer for PD Detection Analysis - Tiengthong, Thanadol; Jaya Marindra, Adi Mahmud; Pattanadech, Norasage; Promwong, Sathaporn (My University, 2022)
The characterization of transformer wall effects a big problem regarding to the partial discharge, which caused substantial business losses and partial discharge analysis. Previously, there were methods of examination and evaluation using ultrasonic and acoustic waves, for this thesis saw the importance of having studied and done. Test the transmission of electromagnetic waves in a power transformer. The vector network analyzer was used to measure and record the results. A microstrip patch antenna was used to evaluate the experimental measurements on the designed transformer wall at different locations. The results obtained from the experiments will be analyzed, evaluated, and compared to the transfer function of the electromagnetic wave in the transformer. Considering the transfer function, power delay profile, and path loss, in the cases of no obstruction and obstruction from the evaluation and comparative consideration. Studies and experiments show that the data obtained measuring electromagnetic wave characteristics in transformers are guidelines in the study and analysis of partial discharges in the transformer. And primary data for the future analysis of partial discharges in the transformer.
Keywords: delay characteristic; partial discharge; propagation loss; transformer; UHF method